Performance simulation and analysis of a multi-energy complementary energy supply system for a novel BIPVT nearly zero energy building. (15th April 2023) - Ren, Haibo; Quan, Zhenhua; Wang, Zhaomeng; Wang, Lincheng; Jing, Heran; Zhao, Yaohua
Highlights: Micro heat pipe array-based BIPVT module enables efficient heat utilization. A novel model of the BIPVT module and energy supply system was established. Highly efficient combination of BIPVT and heat pump utilization is achieved. Summarized the energy-saving features of BIPVT building in different seasons. The novel BIPVT buildings achieve nearly zero energy standards. Abstract: Building integrated photovoltaic–thermal (BIPVT) technology is an efficient form of solar energy utilization, which realizes self-energy supply and holds good development prospects. In this paper, a novel BIPVT module based on micro heat pipe array and BIPVT near-zero energy building are proposed. A matching multi-energy complementary energy supply system is also proposed for this building. The building and energy supply system models were built using TRNSYS. The load characteristics of BIPVT buildings were studied by analyzing the heat transfer process of BIPVT components. The energy-saving rate of the building was also calculated using the method of near-zero energy building evaluation index. The accumulated cooling load and heating load of the buildings throughout the year show that those of the BIPVT buildings are 8.6% higher than those of the benchmark building. Comparison of the energy consumption results shows that the annual cumulative energy consumption of the BIPVT building is 32.3% lower compared to the benchmark building's. In addition, 61.2% of the energy required for year-round refrigeration, heating, and electricity can be supplied by this system. The energy consumption index of the BIPVT building is 70.26 kWh / (m 2 a). Compared with the benchmark building, the BIPVT building energy saving rate is 76.6% and the building energy efficiency improvement rate is 32.3%.